Actions of the asturian educational inspectorate to contribute to the improvement of schools - Figueiras Fernández, Ana María; de la Fuente Martínez, Ángel (Avances en Supervisión Educativa, 2023)
In the 2011-2012 academic year, the Educational Inspectorate of the Autonomous Community of the Principality of Asturias carried out an action linked to its role of participation in the evaluation of the education system, emphasizing the organization and operation of the centers, the teaching and management function, the results, and the preparation of evaluation plans. However, from the following academic year until the present day, this action was relegated to the benefit of the supervision of educational processes, understood as the development of the practice of evaluation that allows the detection of weak points that must be corrected through the proposals for improvement that are considered pertinent. The development of this first action involved the analysis of documentation, the application of questionnaires, interviews, observation in classrooms and, subsequently, submitting the information obtained to a triangulation process which is projected in a report of which the school is aware and from which its management team draws up an improvement plan. The interest of this article is none other than to share a model of action of the Asturian Education Inspectorate, which in the exercise of its functions aims to contribute to helping schools to enhance equity, educational quality and school success.